THE EFFECT OF HR COMPETENCY, MOTIVATION AND THE WORK ENVIRONMENT ON THE PERFORMANCE OF EMPLOYEES IN INSPECTORATE OFFICE OF BANTAENG DISTRICT, SOUTH SULAWESI PROVINCE - Echdar, Saban; Idris, Muhammad; Sabban, Yasrib Putranto (Program Pascasarjana STIE Amkop Makassar, 2020)
This study aims to analyze the influence of human resource competence, motivation and work environment on the performance of the employees of the Inspectorate Office of Bantaeng Regency. The population and sample of this study were 50 employees of the Regional Inspectorate Office of Bantaeng Regency, using a saturated sample and multiple linear regression analysis. The results showed: (1) HR competency has a positive and significant effect on employee performance, as evidenced by the t test value obtained by HR capabilities (X1) of 3.908 where the t test value> the t table value 1.30, (2) work motivation has a positive effect but not significant to employee performance, as evidenced by the t test value on motivation (X2) of 1.519, where the t test value> t table 1.30, (3) The work environment has a positive and significant effect on employee performance, as evidenced by the environmental t test value. Work (X3) of 3,465> t table value of 1.30, with a significant value of 0.001 less than 0.05, (4) HR competence, motivation and work environment have a positive and significant effect simultaneously on employee performance, as evidenced by the results of f count of 39,724 with a significant value of 0,000, where the significant value the t table value is 1.30, and with a sig value of 0.000